Regulation of business activity of the consumer market at municipal level - A. S. Kuznecov (Путеводитель предпринимателя, 2020)
In article actual problems of regulation of business activity in system of ensuring quality and competitiveness of the consumer market at municipal level are considered. A number of the factors which are negatively influencing development and functioning of business activity of the consumer market at municipal level in the Russian Federation are provided.